Żołnierz i służba wojskowa w świetle kościelnych źródeł normatywnych z IV i V wieku - Hołasek, Andrzej (Vox Patrum, 2015)
At the beginning of the fourth century the legal situation of Christians in the Roman Empire changed dramatically. Thanks to the Emperor Constantine they were no longer persecuted, and their faith became religio licita. From that point onwards the views of Christians on the state began to evolve. It was a long-term process, and happened at a varied pace. One of the aspects of this transformation was the change of Christian attitude to military service. It needs to be said that, from this perspective, the Church legislative sources have not been examined in a great detail. This article aims to take a closer look at several of the sources that include Church regulations relating to military service of the fourth and fifth centuries. These include, i.a., Canons of Hippolytus; Letters of St. Basil; Apostolic Constitutions and Canons of the Apostles. In addition, the article discusses the relevant contents of synodal and council canons from said period. These regulations show the adaptation of Church legislature to the new circumstances, in which the Roman state stopped being the persecutor and became the protector of Christianity. The analysis of numerous documents confirms that Christians were present in the Roman army already in the third century. Because of the spilling of blood and the pagan rites performed in the army, the Church hierarchs strongly resisted the idea of allowing Christians to serve in the military. Church regulations from the third century strictly forbade enlisting in the army, or continuing military service for those who were newly accepted into the community, for the reasons mentioned above. From other documents, however, we learn that the number of Christians in the army was nonetheless increasing. Many were able to reconcile military service with their conscience. At the beginning of the fourth century emperor Constantine granted Christians religious freedom. He allowed Christian soldiers to abstain from invoking pagan gods while swearing military oath (sacramentum), and to participate in Sunday services. The empire was slowly becoming a Christian state. It is for this reason that in the Church regulations from the fourth and fifth century we find acceptance for the presence of Christians in the army. Even though killing of an enemy required undertaking penance, it was no longer a reason for excommunication with no possibility of returning to the Christian communion. The Church expected Christian soldiers to be satisfied with their wages alone, and to avoid harming others through stealing, forced lodging or taking food. The Church in the East no longer considered it wrong to accept gifts for the upkeep of clergy and other faithful from the soldiers who behaved in a correct manner. From the mid-fourth century performing religious services started being treated as separate from performing a layperson’s duties. For this reason the bishops, in both parts of the empire, decided that clergy are barred from military service. In the West, those of the faithful who enlisted with the army after being baptised could no longer be consecrated in the future. In the East, the approach was less rigorous, as the case of Nectarius, the Archbishop of Constantinople, shows. By the end of the fourth century, the West adopted very strict rules of public penance for soldiers – the Popes reminded in their letters to the bishops in Spain and Gaul that after performing the public penance, the soldiers were forbidden to return to the army. We should not forget that the change in the attitude of the Church to military service was also affected by the political-military situation of the Empire. During the fourth and fifth centuries its borderlands were persistently harassed by barbarian raids, and the Persian border was threatened. Let us also remember that the army was not popular in the Roman society during this period. For these reasons, the shifting position of the Church had to be positively seen by the Empire’s ruling elites. The situation became dramatic at the beginning of the fifth century, when Rome was sacked by barbarians. Developing events caused the clergy to deepen their reflections on the necessity of waging war and killing enemies. Among such clergymen was St. Augustine, in whose writings we may find a justification of the so-called just war. Meanwhile, in the East, the view that wars can be won only with God’s help began to dominate.